Górny Śląsk - Szturm de Sztrem, Tadeusz (1892–1968) (Państwowe Wydawnictwo Naukowe, 1965)
p. 199-203
Keywords: Silesia, Upper (Poland and Czech Republic) - 1919-1922 - sources; Szturm de Sztrem, Tadeusz (1892-1968) - biography; Polish Socialist Party - biographies

Major Results of 1976 Excavations of Early Medieval Sites in Poland - Tunia, Krzysztof (Zakład Narodowy im. Ossolińskich, 1977)
P. 199-203 : ill. ; 25 cm
Keywords: early Middle Ages -- Poland; early medieval settlement; early medieval cultures; review of archaeological sites -- Poland

Studia z Dziejów Rosji i Europy Środkowo-Wschodniej T. 53 z. 1 (2018), Wytyczne dla autorów, Zasady recenzowania artykułów - Institute of History of the Polish Academy of Sciences (Instytut Historii Polskiej Akademii Nauk, 2018)
Continues: Studia z Dziejów ZSRR i Europy Środkowej
p. 199-203
Keywords: Europe, Central - history - periodicals; Europe, Eastern - history - periodicals; Russia - history - periodicals

Atylostoma tricolor (Mik, 1883), a species new to the fauna of tachinid flies (Diptera: Tachinidae) of Poland - Bystrowski, Cezary; Polska Akademia Nauk. Muzeum i Instytut Zoologii (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 1997)
First record of Atylostoma tricolor (MIK) from Poland was described. Previous information records of this species from Europe were summarised.
Bibliogr. p. 202-203
P. 199-203 : ill. ; 24 cm
Abstract in Polish. Taxa in Latin.
Keywords: Atylostoma tricolor; Konstantynów; Lepidoptera; lepidopterans; butterflies and moths; hosts; Eurrhypara hortulata; species biology; rare species; tachinids; tachina flies; Larvaevoridae; brachyceran flies; Brachycera; insects; Insecta; Diptera; flies; geographical distribution; new taxa to a regional fauna; Poland; Tachinidae

Prey selection in blue tit Parus caeruleus as a response to food levels - Grieco, Fabrizio (1969– ) (Muzeum i Instytut Zoologii PAN, 1999)
Some models of central place foraging relate the time taken to deliver a prey to the selectivity of the forager. If birds have to travel longer, they are expected to take only larger prey. Prey selectivity may also increase if birds have more time available for search activities. I tested this last hypothesis by experimentally increasing the food available to Blue Tits during young rearing. Insect larvae were offered to breeding adults from egg hatching to fledging of the young. Provisioning rates and prey size were studied by videotaping. In experimentally overfed broods, part of the additional food was delivered to their nestlings by the adults, while the rate of feeding with natural prey decreased compared to unmanipulated pairs. Overfed males delivered larger insect larvae than control males, while females showed no response to the treatment. Overfed males could deliver larger prey at late chick ages (when presumably the chicks' demand is higher) than controls, suggesting that control males were time- (or energy) constrained. Moreover, overfed parents appeared to choose relatively more prey that may be important in the chicks' diet. The results show that prey selectivity is related to time (or energy) budgets.
Referat wygłoszony na Second Meeting of the European Ornithologists' Union
Bibliogr. p. 202
P. [199]-203 : ill. ; 27 cm
Abstract in Polish. Taxa in Latin
Keywords: Blue Tit; Netherlands; congresses; minimum acceptable prey size; videotaping; central place foraging models; birds; Cyanistes caeruleus; Parus caeruleus; Paridae; Aves; 1998

Studia z dziejów górnictwa i hutnictwa - Keck, Antonina (Zakład Narodowy im. Ossolińskich, 1962)
p. 199-203
Reviewed book : Studia z dziejów górnictwa i hutnictwa, vol. I-V, ed. Jan Pazdur, Wrocław - Warszawa 1957-1960, Ossolineum, Wydawnictwa Geologiczne. Instytut Historii Kultury Materialnej PAN. Studia i Materiały z Historii Kultury Materialnej.
Keywords: industry; mining; steelworking; material culture